Productive Land Management Through the Concept of Cooperation in the Perspective of Wealth: A Study of the Community of Serdang Bedagai District, Nort Sumatera in the Framework of Sustainable Development Goals - Muhammad Zuhirsyan; Supaino; Rizal Agus; Enny Segarahati Barus; Noradilla binti Osman (Profetika: Jurnal Studi Islam, 2025)
Objective: This study was conducted to find and analyze the phenomenon of productive land management through the concept of cooperation carried out by the community in the Kuta Baru area, Tebing Tinggi Suddistrict, Serdang Bedagai district, North Sumatra in the study of maslahat. Theoretical framework: This study refers to the concept of maslahat in Muamalah Fiqh  and the principles of syirkah and muzara’ah in Islamic economics which emphasize justice, benefit, and sustainability. Literature review: This study refers to the views of classical and contemporary scholars and the hadiths of the Prophet SAW which are the legal basis and practice of syirkah (cooperation) in Islam, such as musyarakah, muzara’ah, and Musaqah, as well as the concept of mashlahah as its normative basis. Methods: The research was conducted through descriptive qualitative study based on welfare with primary data collection through interviews and observations. Interviews were conducted with the village government and several community leaders. Results: The results of the study show that many of the people in this area manage productive land cooperatively between family members to manage the land both to fulfil the economy, living needs and others, both through agricultural cooperation agreements and general business cooperation. This action is an effort to maintain and preserve local culture by continuing to care for agricultural land so that it continues to be fertile and produces benefits for many people. Implications: This finding encourages the need for local policies that support productive land management based on Sharia cooperation, and to strengthen the economic institutions of village communities based on Islamic values. At the same time, this practice supports the achievement of several Sustainable Development Goals, especially SDG 1, SDG 2, SDG 8, SDG 10, and SDG 15. Novelty: This research lies in an integrative approach between the values of welfare, local culture, and Sharia economic practices in the context of agrarian management, which has not been widely studied before. The alignment between Islamic values and global development goals provides a unique and contextual framework for sustainable rural development.